Switzerland : 2004 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Switzerland. (IMF Staff Country Reports; Country Report, 2004)
This 2004 Article IV Consultation highlights that there are signs that the economy of Switzerland has started to grow again on the back of stronger exports and domestic investment and supported by accommodative monetary and fiscal policies. Unemployment has risen, but at 4 percent is low by international standards. Inflation remains negligible and the current account is running a large surplus. Executive Directors have commended the authorities' sound macroeconomic policies that have placed the Swiss economy in a good position to benefit from the nascent global recovery.